Analysis of Queuing Systems at McDonald's Outlets in Malang with an Arena Simulation Approach - Sukram Sukram; P Rahayu; S Nugrowibowo (Widyagama University of Malang, 2023)
The purpose of this research is to analyze the queuing system at McDonald's outlets in Malang City using the Arena simulation approach. The novelty of this research is from the object of research, namely McDonald's in Malang City, which has never been studied before. This research uses quantitative research methods. Data collection techniques were carried out by observation and document study. The data source used in this research is primary data. The population of this study is one of McDonald's drive thru facilities in Malang City. In this study, the sample selection used nonprobability sampling techniques. The data that has been collected is used as input in the Arena simulation to model the queuing system at McDonald's outlets. This research is limited to McDonald's outlets on MT Haryono street, no 115 Malang City, so the results only apply to McDonald's outlets in this area. This research is also limited to a certain period of time according to the research period of August 24, 2023 at 12:00-15:00. The results showed that the average queue duration in the system reached 7.2 minutes. Therefore, the recommendation from the researcher is to increase the number of cashiers, and increase the work efficiency of cashiers during lunch or evening hours to reduce the average queue time. Based on the simulation results, with the addition of one cashier, the average queue time can be reduced by 3.2 minutes, namely to 4 minutes.